2013
DOI: 10.1158/1535-7163.mct-13-0318
|View full text |Cite
|
Sign up to set email alerts
|

A Highly Potent and Specific MET Therapeutic Protein Antagonist with Both Ligand-Dependent and Ligand-Independent Activity

Abstract: Activation of the MET oncogenic pathway has been implicated in the development of aggressive cancers that are difficult to treat with current chemotherapies. This has led to an increased interest in developing novel therapies that target the MET pathway. However, most existing drug modalities are confounded by their inability to specifically target and/or antagonize this pathway. Anticalins, a novel class of monovalent small biologics, are hypothesized to be "fit for purpose" for developing highly specific and… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
23
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 41 publications
2
23
0
Order By: Relevance
“…30 Others have used these U87 cells in a xenograft mouse model and found that specific c-MET antagonists cause dose-dependent tumor growth inhibition. 41 Our results show that targeting HIF-1a leads to reduced c-MET protein levels, which corroborates the results of studies that have shown that this also occurs in breast and lung cancer cell lines. 12 It may be that disrupting HIF-1 function in gliomas, and thus c-MET, will not lead to the same invasion and metastasis encountered in anti-VEGF therapy.…”
supporting
confidence: 91%
“…30 Others have used these U87 cells in a xenograft mouse model and found that specific c-MET antagonists cause dose-dependent tumor growth inhibition. 41 Our results show that targeting HIF-1a leads to reduced c-MET protein levels, which corroborates the results of studies that have shown that this also occurs in breast and lung cancer cell lines. 12 It may be that disrupting HIF-1 function in gliomas, and thus c-MET, will not lead to the same invasion and metastasis encountered in anti-VEGF therapy.…”
supporting
confidence: 91%
“…Importantly, anticalins retain the overall fold of lipocalins but exhibit redesigned pharmacologic properties (6). We rationally engineered PRS-110 (Pieris AG), an anticalin with monovalent specificity for MET (binding affinity of 0.6 nmol/L determined by kinetic exclusion assay) (7), which is based on the tear lipocalin scaffold. PRS-110 acts as both a full antagonist of HGF-evoked MET signaling (half maximal inhibitory concentration [IC 50 ] of 35 nmol/L in HUVEC pMet assay) and also a ligand-independent inhibitor of MET-driven tumorigenesis.…”
mentioning
confidence: 99%
“…PRS-110 acts as both a full antagonist of HGF-evoked MET signaling (half maximal inhibitory concentration [IC 50 ] of 35 nmol/L in HUVEC pMet assay) and also a ligand-independent inhibitor of MET-driven tumorigenesis. PRS-110 is being developed as a therapeutic and in this form is site-specifically conjugated to a branched 40-kDa polyethyleneglycol (PEG) (2 · 20 kDa PEG) moiety for half-life prolongation (7). PRS-110 also displays many highly desirable properties as an imaging agent.…”
mentioning
confidence: 99%
“…Caki1 cells are a low-VHL-expressing cell line and form subcutaneous (s.c.) tumors with long periods of latency and do not metastasize. We used Caki1 cells, which we also used in our in vitro work, for in vivo studies, since they are low-VHL-expressing cells and are frequently used by others for animal studies of RCC (36)(37)(38). We injected Caki1 cells stably transduced with shGFP, shARC no.…”
Section: Resultsmentioning
confidence: 99%